A comparative study on details of green walls in different climates - M. Mahmoudi Zarandi; M. Pourmousa (Environmental Resources Research, 2018)
Global warming has today turned to one of the most important environmental issues due tooveruse of fossil fuels, and it needs serious attention. Since the mid-1970s, an urgent needwas therefore felt around the world to reduce the use of energy for heating and cooling inbuildings. Using green covers, especially green facades, in appropriate environmentalconditions can be regarded as a method to achieve thermal comfort while maintaining thebuilding energy consumption low as well as reducing greenhouse gases emission. Thepresent paper investigates the features related to living walls in different climates. Based onresults, due to reduced heat absorption, evaporative cooling and low thermal conductivity,the hotter and drier the climate, the higher the efficiency of the green wall as well astemperature reduction will be. On the other hand, using of green walls in temperate and hotand humid climates has a positive effect, but because of the humidity factor, open or closedair layers should also be considered. The green wall surface creates more stable relativehumidity in the air layer near the wall surface without increasing the relative humidity ofindoor air. At the urban scale in the warmer and drier climates, the green covers will have adramatic effect on urban temperatures. Using green covers of buildings’ walls, there will bea significant potential for reducing urban temperatures, while the highest efficiency will beachieved with simultaneous application of green surfaces for both roofs and walls.